Indicadores da paisagem para a ocorrência de sítios arqueológicos na área arqueológica de Serra Negra, face leste do Espinhaço - Leonardo Mateus Pfeilsticker de Knegt (2015)
The Espinhaço Mountain Range is a geographic landmark for Minas Gerais State, and its relevance goes from the landscape features through its cultural aspects. Thus, the archeological sites located in the Espinhaço were, and still are, studied to get a better knowledge regarding the regional archeological background. The Eastern side of the Espinhaço mountain range still is a boundary that needs to be explored regarding archeological studies and only recently the region began to be studied. The results of these studies point to the existence of archeological sites with characteristics different from the ones found in other Espinhaços regions. Being so, the study focused on the Eastern side of the Espinhaço range with the purpose to point out which areas have the highest predisposition for the existence of archeological sites to aid and foster further and future studies in the region and to do so, the landscape was analyzed geographically in search of geoenvironmental elements that could indicate the existence, or not, of archeological sites. Previously identified sites served as basis for the valuation of the data that fed the predictive model based on multi-criteria analysis. The geographic analysis indicated the existence of eleven landmarks in the study area that are the basis for the description of local geography. The final result encompasses not only the predictive model, but also a geographic analysis of the region aiming to understand which geoenvironmental variables are beneficial for populations fixation in the area and the description of the geographic data collected during the study.